2019
DOI: 10.12740/pp/onlinefirst/91298
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body cryotherapy – promising add-on treatment of depressive disorders

Abstract: Cel pracyNadal istnieje zapotrzebowanie na nowe, efektywne biologiczne interwencje terapeutyczne w epizodach depresyjnych i zaburzeniu depresyjnym nawracającym. Krioterapia ogólnoustrojowa (WBC), będąca formą stymulacji ogólnoustrojowej temperaturami kriogenicznymi, jest coraz częściej stosowaną metodą leczniczą w schorzeniach neurologicznych oraz w reumatologii. Badanie miało na celu określenie skuteczności krioterapii ogólnoustrojowej jako augmentacji leczenia epizodu depresyjnego.MetodaDo badania obserwacyj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Indeed, our present findings confirm the results of earlier studies of Rymaszewska et al (19,20), and also our preliminary report (21). In 2012, Misiak et al (52) suggested translation WBC into the prevention of MCI and Alzheimer's disease.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Indeed, our present findings confirm the results of earlier studies of Rymaszewska et al (19,20), and also our preliminary report (21). In 2012, Misiak et al (52) suggested translation WBC into the prevention of MCI and Alzheimer's disease.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the majority of participants were female. As we recently discussed (21), it might influence the cytokines index. It should also be noted that 2 weeks of cryotherapy may be profitable to health, for example, through the displacement of loneliness or lack of any social activity.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“… 7 ), and patients with atopic dermatitis. 8 Importantly, WBC has very recently been shown to positively influence cognitive functioning and mental health, with studies indicating significant alleviation of depressive symptoms in clinically diagnosed depressed patients 9 and memory improvements in patients with mild cognitive impairment. 10 Finally, WBC is used more and more frequently as a wellness method in healthy subjects to help maintain good health (e.g., 11 ).…”
Section: Introductionmentioning
confidence: 99%